AN ANALYSIS OF CODE-SWITCHING USED BY ALUMNI OF THE INTERNATIONAL INDONESIAN SCHOOL OF JEDDAH (IISJ) - Daenah Daenah; Afiifah Al Rosyiidah (Jurusan Sastra Indonesia, 2022)
This study represents the types and reasons for code-switching used by Alumni of IISJ. It was conducted using descriptive research. IISJ’s Alumni use all types of code-switching; tag-switching (6), intersentential-switch (25), and intrasentential-switch (19). Additionally, 7 reasons for code-switching occured; filling the linguistic needs (17), continuing the last language used (7), specifying addressee (4), qualifying message (9 data), specifying speaker involvement (5), marking and emphasizing group identity (5), conveying confidentiality, anger, and annoyance (3).